4‐4: Flexible Quantum Dot Color Converter Film for Micro‐LED Applications. Issue 1 (29th May 2019) - Bai, Xue; Yang, Hongcheng; Zhao, Bingxin; Zhang, Xiaoli; Li, Xiang; Xu, Bing; Wei, Feng; Liu, Zhaojun; Wang, Kai; Sun, Xiao Wei
Abstract : This paper introduces a flexible and uniformly‐dispersed quantum dot (QD) color converter (QDCC) fabricated for micro‐LED based on photolithography. Compared to the original QDCC, the modified QDCC (chemical compatible to photoresist) exhibited high quantum yield (QY) up to 60%‐70%, and a high optical density（OD）over 1.5.